Blood-tumor barrier opening by MRI-guided transcranial focused ultrasound in a preclinical breast cancer brain metastasis model improves efficacy of combinatorial chemotherapy - Arsiwala, Tasneem A.; Blethen, Kathryn E.; Wolford, Cullen P.; Panchal, Dhruvi M.; Sprowls, Samuel A.; Fladeland, Ross A.; Kielkowski, Brooke N.; Pritt, Trenton A.; Wang, Peng; Wilson, Olivia; Carpenter, Jeffrey S.; Finomore, Victor; et al. (Frontiers in Oncology, 2023)
Patients with metastatic breast cancer have high and continually increasing rates of brain metastases. During the course of the disease, brain metastases can occur in up to 30% of these patients. In most cases, brain metastases are diagnosed after significant disease progression. The blood-tumor barrier increases the difficulty of treating brain metastasis by preventing accumulation of chemotherapy within metastases at therapeutically effective concentrations. Traditional therapies, such as surgical resection, radiotherapy, and chemotherapy, have poor efficacy, as reflected by a low median survival rate of 5-8% after post-diagnosis. Low-intensity focused ultrasound (LiFUS) is a new treatment for enhancing drug accumulation within the brain and brain malignancies. In this study, we elucidate the effect of clinical LiFUS combined with chemotherapy on tumor survival and progression in a preclinical model of triple-negative breast cancer metastasis to the brain. LiFUS significantly increased the tumor accumulation of 14C-AIB and Texas Red compared to controls (p< 0.01). LiFUS-mediated opening of the BTB is size-dependent, which is consistent with our previous studies. Mice receiving LiFUS with combinatorial Doxil and paclitaxel showed a significant increase in median survival (60 days) compared to other groups. LiFUS plus combinatorial chemotherapy of paclitaxel and Doxil also showed the slowest progression of tumor burden compared to chemotherapy alone or individual chemotherapy and LiFUS combinations. This study shows that combining LiFUS with timed combinatorial chemotherapeutic treatment is a potential strategy for improving drug delivery to brain metastases.